Falkor, the coiled terror - Blade, Adam (Blade, Adam. Beast quest special edition., 2016)
Only a mighty magic could awaken the ancient snake-Beast Falkor. But when things go awry in Avantia, it seems the Beast's power has fallen into the wrong hands. Tom and Elenna must seek Falkor in his lair if they are to keep the kingdom safe from this dark force. Don't miss this new bumper special edition of the bestselling series!